Prevalence of HBsAg and Anti HCV Sero-Positivity among Healthy Bangladeshi Job Seekers in Gulf States and KSA (Bangladesh Medical Journal, 2011)
DOI: 10.3329/bmj.v39i2.7035Bangladesh Medical Journal 2010, 39(2) pp.35-39